The effect of synthesis conditions and process parameters on aerogel properties - Payanda Konuk, Ozge; Alsuhile, Ala A. A. M.; Yousefzadeh, Hamed; Ulker, Zeynep; Bozbag, Selmi E.; García-González, C. A.; Smirnova, I.; Erkey, Can (Frontiers in Chemistry, 2023)
Aerogels are remarkable nanoporous materials with unique properties such as low density, high porosity, high specific surface area, and interconnected pore networks. In addition, their ability to be synthesized from various precursors such as inorganics, organics, or hybrid, and the tunability of their properties make them very attractive for many applications such as adsorption, thermal insulation, catalysts, tissue engineering, and drug delivery. The physical and chemical properties and pore structure of aerogels are crucial in determining their application areas. Moreover, it is possible to tailor the aerogel properties to meet the specific requirements of each application. This review presents a comprehensive review of synthesis conditions and process parameters in tailoring aerogel properties. The effective parameters from the dissolution of the precursor step to the supercritical drying step, including the carbonization process for carbon aerogels, are investigated from the studies reported in the literature.